Circulating prolactin and in situ breast cancer risk in the European EPIC cohort: a case-control study. Issue 1 (December 2015) - Tikk, Kaja; Sookthai, Disorn; Fortner, Renée; Johnson, Theron; Rinaldi, Sabina; Romieu, Isabelle; Tjønneland, Anne; Olsen, Anja; Overvad, Kim; Clavel-Chapelon, Françoise; Baglietto, Laura; Boeing, Heiner; et al.
Abstract Introduction The relationship between circulating prolactin and invasive breast cancer has been investigated previously, but the association between prolactin levels andin situ breast cancer risk has received less attention. Methods We analysed the relationship between pre-diagnostic prolactin levels and the risk ofin situ breast cancer overall, and by menopausal status and use of postmenopausal hormone therapy (HT) at blood donation. Conditional logistic regression was used to assess this association in a case-control study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort, including 307in situ breast cancer cases and their matched control subjects. Results We found a significant positive association between higher circulating prolactin levels and risk ofin situ breast cancer among all women [pre-and postmenopausal combined, ORlog2 = 1.35 (95% CI 1.04-1.76), Ptrend = 0.03]. No statistically significant heterogeneity was found between prolactin levels andin situ cancer risk by menopausal status (Phet = 0.98) or baseline HT use (Phet = 0.20), although the observed association was more pronounced among postmenopausal women using HT compared to non-users (Ptrend = 0.06vs Ptrend = 0.35). In subgroup analyses, the observed positive association was strongest in women diagnosed within situ breast tumors <4 years compared to ≥4 years after blood donation (Ptrend = 0.01vs Ptrend = 0.63; Phet = 0.04) and among nulliparous women compared to parous women (Ptrend = 0.03vs Ptrend = 0.15; Phet = 0.07). Conclusions Our data extends prior research linking prolactin and invasive breast cancer to the outcome ofin situ breast tumours and shows that higher circulating prolactin is associated with increased risk ofin situ breast cancer.